Evolutionary Ecology of Lizards (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Except for latitudinal and elevational extremes, lizards range across a vast variety of biotopes worldwide, including environments as disparate as deserts, prairies, temperate woodlands, rainforests, or anthropic habitats. Although most species thrive on the ground, numerous lizards are fossorial, arboreal, and even aquatic, found in either fresh- or seawater. With lizards being ectotherms, accurate thermoregulation and other physiological adaptations are in most cases fundamental for their survival in such a variety of habitats. Moreover, lizard coloration may mediate thermoregulation, reproduction, and social status, among others. Lizards have also evolved some unusual antipredator adaptations, such as tail autotomy. Consequently, the astonishing morphological, ecological, and functional diversity of lizards results from extremely intense selective pressures, oftentimes opposing, many of whose interrelationships have yet to be disentangled. This Special Issue provides the international scientific community with an integrative meeting point to discuss and synthesize the current knowledge on the evolutionary pathways and mechanisms that led to today’s lizards.